Audiodescrição: Ad como recurso didático no ensino da química - Pimentel, Silvia Janaina de Oliveira (2023)
The master's research, proposed here, is part of the Graduate Program in Technological Education of the Federal Institute of Education, Science and Technology of Amazonas-PPGET/IFAM/CMC and is aimed at visually impaired students inserted in inclusive teaching classes medium, without, however, being restricted to this public. Audiodescription is a communication accessibility resource for people with visual impairments that aims to describe image information in words, based mainly on Mota (2012, 2016), Mianes (2016), Lima (2010, 2013) Perdigão (2017) and Vergara Nunes (2016). It has already established parameters, based on the contexts in which it was used, and these have served as guidelines for its use in other spaces, Filho, Machado, Nunes (2017) and Ribeiro (2020), among them, teaching, Nunes (2016). To be adapted to teaching, it is understood that there is a need to think about other parameters for this area, since those that exist do not dialogue directly with didactic pedagogical issues, bringing implications for student learning. Therefore, the research problem consists, based on what has already been established about Audiodescription of static images, to look into the possibility of developing and proposing specific parameters for teaching, taking chemistry as the space for their construction. . Thus, the main point of the study is to develop guiding parameters for the use of Audiodescription as a didactic resource for accessibility in science teaching, with a focus on chemistry teaching. It should be noted that the choice of this subject was due, above all, to the difficulty that students in general have in this field, claiming that they cannot understand chemistry nor understand the importance of their learning for life. In this context, the proposal brings the Pedagogical Didactic Audiodescription, which has the transversal characteristics necessary for the teaching/learning of visually impaired students in inclusive classrooms. The research methodology will be qualitative, Chizzotti (2000), using action research, Thiollent (2005), for data collection and design thinking, Ferreira (2020), to treat the data through its stages: understanding the problem, design solutions, prototype and implementation to generate an educational product. Audiodescription mini-courses and workshops were held in order to identify points relevant to the construction of the educational product.